2.5k views
4 votes
I need help finding the inverse of this problem

I need help finding the inverse of this problem-example-1
User Pheven
by
7.1k points

1 Answer

4 votes


y=√(x-1)+6

(Notice that we always have
y\ge6[tex].)</p><p>Swap [tex]x and
y, then solve for
y:


x=√(y-1)+6


x-6=√(y-1)


(x-6)^2=(√(y-1))^2


(x-6)^2=y-1


y=(x-6)^2+1 (this is the inverse)

###

This inverse is valid only for
x\ge6. Why?

Suppose we take
x=0. Then


y=(0-6)^2+1=37

This would suggest that in the original equation, we should get
x=37 when
y=0. But when we check this, we end up with


0=√(37-1)+6=√(36)+6=6+6=12

which is clearly not true.

User Walid Hanafy
by
5.4k points